Análise da gestão de resíduos sólidos em um supermercado da cidade de Itacoatiara – Am - Isper, Gabrielle Konne Pinheiro (Brasil, 2024)
Taking into consideration the increase in concerns regarding business environmental impacts, changes in the population's consumption behavior and the participation of the supermarket sector in the production of solid waste, the following work proposes an assessment of solid waste management in a large supermarket located in the city of Itacoatiara-AM. To this end, methodological procedures of semi-structured interviews and simple non-participatory observations were used, in addition to the use of information provided by the National Solid Waste Policy (Federal Law 12,305/2010). After analysis, the main results identified were presented, which included good solid waste treatment measures, with the exception of fat oil, batteries and lamps, as well as the absence of a Solid Waste Management Plan (PGRS) and lack of knowledge of the final destination of waste carried by third parties. It was suggested a series of recommendations, including that a PGRS be drawn up to suit the reality of the establishment, the application of Reverse Logistics, a partnership with the city's Association of Recyclable Material Collectors and the inclusion of the promotion of sustainable actions for customers.